Obrazy kobiecości w perspektywie geopoetyki ludowych powieści Józefa Ignacego Kraszewskiego = Images of femininity in the perspective of geopoetics of folk novels by Jozef Ignacy Kraszewski - Woźniak, Jesica (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article, using selected geopoetics` tools, examines images of femininity from a series of eight folk novels by Jozef Ignacy Kraszewski, created in the 1840s. The analysis and interpretation is centered on the literary equivalents and language examples of the link between the work and geographic and regional features as one of the overarching determinants of characters behavior.
Keywords: woman; folk novel; Kraszewski, Józef Ignacy (1812-1887); geopoetics; kobieta; powieść polska - 19 w.; geopoetyka